2009
DOI: 10.1270/jsbbs.59.373
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of genetic variation for aluminium resistance and polyphenol oxidase activity in genebank accessions of spelt wheat

Abstract: Spelt wheat [Triticum aestivum ssp. spelta (L.) Thell.] is becoming a valuable crop due to its reputation as a healthy food. In Australia, this crop has not been targeted for systematic breeding. Identification of spelt genotypes having low PPO activity and resistance to acid soils (Al 3+ ) are desirable attributes for future cultivar development. We evaluated 51 genebank accessions of spelts from the Australian Winter Cereals Collection for polyphenol oxidase (PPO) activity and for resistance to aluminium (Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…In addition, genetic variation in bread‐making quality (An et al, 2005; Caballero et al, 2001, 2004), protein concentration (Gomez‐Becerra et al, 2010; Stallknecht et al, 1996), lipid content (Ruibal‐Mendieta et al, 2002) and mineral nutrient concentrations (e.g., Zn, Fe, and Se) (Gomez‐Becerra et al, 2010; Ruibal‐Mendieta et al, 2005; Zhao et al, 2009), has been reported. Spelt also shows resistance to abiotic and biotic stresses, such as aluminium (Raman et al, 2009), flooding (Burgos et al, 2001b), leaf rust (Dyck and Sykes, 1994; Mohler et al, 2012; Wang et al, 2010), yellow rust (Sun et al, 2002), leaf and glume blotch (Aguilar et al, 2005; Simon et al, 2010). Many genes and quantitative trait loci (QTL) associated with bread‐making quality and stress resistance have been identified from spelt (Aguilar et al, 2005; Burgos et al, 2001a; Guzman et al, 2012; Mohler et al, 2012; Zanetti et al, 2001).…”
mentioning
confidence: 99%
“…In addition, genetic variation in bread‐making quality (An et al, 2005; Caballero et al, 2001, 2004), protein concentration (Gomez‐Becerra et al, 2010; Stallknecht et al, 1996), lipid content (Ruibal‐Mendieta et al, 2002) and mineral nutrient concentrations (e.g., Zn, Fe, and Se) (Gomez‐Becerra et al, 2010; Ruibal‐Mendieta et al, 2005; Zhao et al, 2009), has been reported. Spelt also shows resistance to abiotic and biotic stresses, such as aluminium (Raman et al, 2009), flooding (Burgos et al, 2001b), leaf rust (Dyck and Sykes, 1994; Mohler et al, 2012; Wang et al, 2010), yellow rust (Sun et al, 2002), leaf and glume blotch (Aguilar et al, 2005; Simon et al, 2010). Many genes and quantitative trait loci (QTL) associated with bread‐making quality and stress resistance have been identified from spelt (Aguilar et al, 2005; Burgos et al, 2001a; Guzman et al, 2012; Mohler et al, 2012; Zanetti et al, 2001).…”
mentioning
confidence: 99%
“…In the last decades, spelt wheat (Tritium spelta L.) has become an attractive species in research and breeding programmes of cereals because of many beneficial traits of its; high nutritional value, wide adaptability, abiotic stress tolerance, high tillering ability and biomass production [1][2][3][4][5]. In organic farming system, spelt is one of the most preferred species due to these attributes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, due to some special advantageous agronomic traits, i.e., wide adaptability, tillering ability, abiotic stress tolerance, and high biomass, the growing area of spelt wheat increased year by year [1,2,3,4]. In the organic farming system, spelt wheat is an attractive species because of the above-mentioned traits.…”
Section: Introductionmentioning
confidence: 99%